2018
DOI: 10.4149/neo_2018_170315n184
|View full text |Cite
|
Sign up to set email alerts
|

AFP role in predicting recurrence of hepatocellular carcinoma after living donor liver transplantation in HCV patients

Abstract: HCC is one of the leading causes of death worldwide. Liver transplantation including living donor transplantation is the best available treatment. We have analyzed our experience with LDLT (living donor liver transplantation) in patients with HCC and HCV in order to determine if alpha feto-protein (AFP) is a better predictor of recurrence than the tumor burden. We have identified all patients with HCV related liver disease and HCC who have undergone LDLT in one center during the period from December 2000 to De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Two large registry studies identified (lab) MELD score as an independent predictor of post‐LT mortality, with tumor relapse being the predominant cause . In addition, it was shown to correlate with tumor angioinvasiveness and HCC recurrence …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two large registry studies identified (lab) MELD score as an independent predictor of post‐LT mortality, with tumor relapse being the predominant cause . In addition, it was shown to correlate with tumor angioinvasiveness and HCC recurrence …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to unpredictable determinants like donor status, allograft quality, and surgical trauma, the patients’ functional status and performance may be accurately assessed . In this context, pre‐LT background liver cirrhosis and related hepatic dysfunction are increasingly assumed to worsen post‐LT tumor‐specific outcome, most probably by induction of cancerogenic proinflammatory and immune‐depressive mechanisms . The albumin‐bilirubin (ALBI) score has recently been established as a novel evidence‐based and easily available tool for the assessment of hepatic functional reserve .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of novel biomarkers, such as AFP [41, 42], glypican 3 [43], Osteopontin [44], CXCL1 [45], UQCRH [46], TIP30 [47], neutrophil–lymphocyte ratio [48], have emerged for diagnosing HCC and predicting patient outcome. Among these biomarkers, AFP is a well-known serum diagnostic and prognostic biomarker for HCC [49].…”
Section: Discussionmentioning
confidence: 99%
“…)MELD score as an independent predictor of microvascular invasion (MVI) on explant pathology, which in turn was the most important factor of poor cancer-specific outcome. Others have recently confirmed the oncological significance of background cirrhosis severity in the liver transplant setting [52][53][54] . In a series of 243 transplant candidates with HCC, Faitot et al [55] demonstrated that clinically evident portal PH was an independent promoter of drop out from the waiting list due to tumor progression.…”
Section: Background Liver Cirrhosismentioning
confidence: 91%
“…Komorowski et al . [53] 142 (lab.) MELD score Apart from AFP level, pretransplant calculated MELD score turned out to be an independent and significant predictor of RFS (HR = 1.16)…”
mentioning
confidence: 99%